Preliminary assessment of root systems morphology in Musa - Blomme, Guy; Ortíz, R. (International Society for Horticultural Science, 2000)
The root system development of 11 genotypes from six diverse Musa groups was studied in detail at IITA High Rainfall Station (Onne, southeastern Nigeria). Plantain hybrids (TMPx 548-9, TMPx 1658-4) were compared with their maternal French plantain landrace (Obino l' Ewai) and their paternal diploid bananas (Calcutta 4 and Pisang Lilin). These were also compared with cooking banana cultivars (Cardaba and Fougamou), a cooking banana hybrid (FHIA 3), dessert bananas (Valery and Yangambi Km 5) and a False Horn plantain landrace (Agbagba). Plants were examined during the vegetative phase in both sole crop and alley cropping fields. Both plantain hybrids had comparable number of primary roots to the plantain landraces and the unrelated cooking bananas. However, the total root length of the plantain hybrids was larger than that of the maternal plantain landrace. Diploid and dessert bananas had the lowest number of primary roots while the dessert bananas also had the lowest total root length. The average diameter of primary roots ranged from 4.3 mm (dessert bananas) to 7.6 mm (Agbagba). Most genotypes had their roots in the 0 cm to 15 cm soil layer. Roots were not found deeper than 80 cm. Sub-horizontal roots reached 3 m occasionally